2006
DOI: 10.1016/j.jacc.2006.04.099
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Pacing Lead Location Alters Systemic Hemodynamics and Left Ventricular Function in Patients With and Without Reduced Ejection Fraction

Abstract: Right ventricular pacing worsens LV function in patients with and without LV dysfunction unless the RV pacing site is optimized. Left ventricular and BiV pacing preserve LV function in patients with EF >40% and improve function in patients with EF <40% despite no clinical indication for BiV pacing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
2
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(123 citation statements)
references
References 33 publications
3
111
2
5
Order By: Relevance
“…10 Liebermann et al also found no correlation between the QRS width and the hemodynamic effect of a given RV pacing site. 25 In our study ventricular lead position during the implantation procedure was verified only on the basis of fluoroscopy and the QRS width compared several days after implantation did not differ between groups. Because QRS duration represents biventricular electrical activation, changes in determinants of cardiac function, such as the sequence of activation and intraventricular synchrony, are not necessarily translated into changes in the length of the QRS.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…10 Liebermann et al also found no correlation between the QRS width and the hemodynamic effect of a given RV pacing site. 25 In our study ventricular lead position during the implantation procedure was verified only on the basis of fluoroscopy and the QRS width compared several days after implantation did not differ between groups. Because QRS duration represents biventricular electrical activation, changes in determinants of cardiac function, such as the sequence of activation and intraventricular synchrony, are not necessarily translated into changes in the length of the QRS.…”
Section: Discussionmentioning
confidence: 62%
“…In the study of Lieberman et al the authors assessed the influence of several RV pacing sites (apex, free wall and septum) on global cardiac performance, and found that RV pacing worsens LV function unless the pacing site is optimized. 25 There were substantial inter-individual variations in the optimal RV pacing site, and no consistent site was superior to others. These observations support results from our study.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, none of the parameters investigated in this study (electric mapping, hemodynamic, regional strains, efficiency) showed a significant difference between RV apical and RV septal pacing. Similarly, no apparent benefit of RV septal pacing over RV apical pacing was observed in a human clinical study of LV pressure-volume loops that also used purely anatomic lead positioning (Lieberman et al, 2006). In the same way, a recent comparison of chronic RV apex and RV septal pacing, based entirely on lead position, showed that RV septal pacing was associated with more impaired circumferential strain and worse LV dyssynchrony than apical pacing (Ng et al, 2009).…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 98%
“…RV pacing has been shown to improve symptoms, exercise capacity, quality of life and survival in these patients (Gammage et al 1991;Lamas et al 1995;Sweeney et al 2007). However, permanent RV pacing has been associated with an increased risk of LV dysfunction, hospitalization, HF, and death (Hayes et al 2006;Lieberman et al 2006;O'Keefe et al 2005;Sweeney et al 2003;Tse and Lau 1997;Wilkoff et al 2002). In 2002, the results of the DAVID trial revealed that RV paced patients with LV dysfunction, requiring a defibrillator, who were actively paced in DDDR-70 mode had a 60% greater risk for hospitalization or death than patients who received minimal back-up pacing in VVI-40 mode (Wilkoff et al 2002).…”
Section: Effects Of Rv Pacingmentioning
confidence: 99%